Secondary data analysis - Vartanian, Thomas P. (New York ; Oxford : Oxford University Press, 2011)
This pocket guide provides an in-depth introduction to 29 of the most widely used data sets in social work and the social sciences. Readers will find information about each data set, how to locate and use the data, what types of questions the data may answer, and the key variables in the data.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Research; Social service -- Statistical methods